The Effect of Board of Director Composition and Audit Committee Expertise on The Real Earnings Management in Indonesia - Feby Astrid Kesaulya; Weny Putri; Dewi Sri (Faculty of Economics and Business Universitas Muhammadiyah Riau, 2020)
The Objective of this research was to prove that the implementation of good corporate governance will have an effect on the real activities manipulation which was done by the management. The implementations of good governance used by this research are board of director composition and audit committee expertise. This research was conducted in Indonesia by using 306 firm years’ observations. The result of this research showed a different result from previous researches. This research showed that the implementation of good corporate governance in the form of board director composition and audit committee expertise do not impact the practice of real activities manipulation. Or, in other words some of the good corporate governance tool could not mitigate the real activities manipulation in the company.